Comparative changes in problematic smartphone use tendencies across four active exercise modalities among college students: an exploratory multicategorical relative indirect-effect analysis - Bin Dai; Canzhong Ji; Tingting Zhong (Frontiers in Psychology, 2026)
Objective To compare pre–post changes in problematic smartphone use tendencies and emotion regulation across four exercise modalities and examine whether cognitive reappraisal and expressive suppression changes accounted for between-modality differences in SAS-SV reduction. Methods Ninety college students were assessed; five were excluded before randomization for exercise contraindications, and 85 were randomized to aerobic training, strength training, VR-based gamified exercise, or combined training. Seventy-seven participants completing both assessments and at least 80% of sessions entered a modified per-protocol complete-case analysis; no intention-to-treat analysis was conducted. All groups completed a 12-week intervention. Outcomes were assessed pre and post-intervention. Group differences were examined using mixed-design ANOVA, followed by exploratory multicategorical parallel mediation with aerobic training as the reference. Results SAS-SV scores and expressive suppression decreased, whereas cognitive reappraisal increased, in all groups. Significant time × group interactions occurred for SAS-SV, F (3, 73) = 45.205, p < 0.001, partial η 2 = 0.650; cognitive reappraisal, F (3, 73) = 21.992, p < 0.001, partial η 2 = 0.475; and expressive suppression, F (3, 73) = 18.860, p < 0.001, partial η 2 = 0.437. The combined group showed the largest changes. Relative to aerobic training, total indirect effects were 0.722 for strength training, 1.253 for VR-based exercise, and 1.916 for combined training; mediator-specific indirect effects were nonzero for all contrasts. Conclusion The four modalities were associated with different magnitudes of pre–post change, with combined training showing the largest changes. Without diagnostic selection or a non-exercise control, the findings concern problematic smartphone use tendencies in a college-student sample and do not establish exercise-specific effects or causal mediation.